PENGEMBANGAN PAPAN MAGNETIK KARIOTIPE PADA MATERI MUTASI KROMOSOM SISWA KELAS XII - SHOMA ADHI WIJAYA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Implementation of curriculum 2013 had a lot constraints, namely some material requires learning media to reach the goal of basic competencies, for example chromosome mutation material. Biology teacher of SMAN Kesamben stated that they facing difficulty in presenting the chromosome mutation material. Observation indicated that 84.3% of students said it was difficult to learn complex concepts and 100% of students required the learning media to help concepts understanding. Karyotype magnetic board is kind of learning media that able to solve that problem. The purpose of this study was to determine the feasibility of karyotype magnetic board media theoretically based on the results of the media validation and empirically based on student responses and student learning outcomes. Research and Development (R&D) method was used in this study. The media development was started on November 2013 to April 2014 in the Department of Biology, FMIPA, State University of Surabaya. Media trial was conducted in SMAN Kesamben Jombang on March 18, 2014. The results showed the quality aspect of media got a percentage of 98.25%, the effectiveness aspect of the media got a percentage of 93.25%, the material aspect of the concept got a percentage of 97.5%, and aspect of language got a percentage of 100%. All of them included into very well criteria. Overall the karyotype magnetic board media is good based on theoretical feasibilty with a percentage of 97.8%. Empirical feasibility got percentage of 95.48% and 100% based on student responses and learning outcomes, respectively. Classical completeness average score is 89.25. Keywords: development, karyotype magnetic board media, chromosome mutation.